Low incidence of livestock-associated methicillin-resistant Staphylococcus aureus bacteraemia in The Netherlands in 2009. - Brigitte A G L van Cleef; Birgit H B van Benthem; Anja P J Haenen; Thijs Bosch; Jos Monen; Jan A J W Kluytmans (PLoS ONE, 2013)
Methicillin-resistant Staphylococcus aureus (MRSA) is a worldwide problem in both hospitals and communities all over the world. In 2003, a new MRSA clade emerged with a reservoir in pigs and veal calves: livestock-associated MRSA (LA-MRSA). We wanted to estimate the incidence of bacteraemias due to LA-MRSA using national surveillance data from 2009 in the Netherlands. We found a low incidence of LA-MRSA and MRSA bacteraemia episodes, compared to bacteraemias caused by all S. aureus (0.04, 0.18 and 19.3 episodes of bacteraemia per 100,000 inhabitants per year, respectively). LA-MRSA and MRSA were uncommon compared to numbers from other countries as well. MRSA in general and LA-MRSA in specific does not appear to be a public health problem in the Netherlands now. The low incidence of LA-MRSA bacteraemia episodes may best be explained by differences in the populations affected by LA-MRSA versus other MRSA. However, reduced virulence of the strain involved, and the effectiveness of the search and destroy policy might play a role as well.